DESIGNING READING MATERIAL BASED ON NORTH SUMATRA STATE MUSEUM - Yenita Br Sembiring; Sulastri Sitanggang; Novia Magdalena Turnip; Grecia Sri Dame Br Manik; Ira Maria Fran Lumbanbatu (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2023)
One crucial step in promoting cultural and historical education in the area is the creation of reading materials about the North Sumatra State Museum. The purpose of this research project was to design and develop reading materials suitable for the museum setting in order to raise public awareness and appreciation of the region's rich cultural and historical legacy. A qualitative technique is used in the research, involving document analysis, interviews, and observation. The resultant reading material can enhance the museum experience by being a useful tool for both formal and informal education. The outcome of this study is a reading guide with comprehensive details about the museum's artifact collection, local history, and the significance of cultural elements. It is hoped that the outcome of this effort will increase public awareness of the North Sumatra State Museum as a knowledge hub that is crucial to the documentation and preservation of the rich cultural heritage of the region, as well as spark interest in and understanding of the area's cultural and historical heritage.